Synthesis of Novel Azo-Linked 5-Amino-Pyrazole-4-Carbonitrile Derivatives Using Tannic Acid–Functionalized Silica-Coated Fe3O4 Nanoparticles as a Novel, Green, and Magnetically Separable Catalyst - Pashaki, Farhad Sedighi; Nikpassand, Mohammad (Frontiers in Chemistry, 2021)
Tannic acid–linked silica-coated Fe3O4 nanoparticles (Fe3O4@SiO2@Tannic acid) were prepared and characterized by transmission electron microscope (TEM), field emission scanning electron microscope (FE-SEM), X-ray powder diffraction (XRD), X-ray spectroscopy (EDX), vibrating sample magnetometry (VSM), and Fourier transform infrared (FT-IR) spectroscopy. Fe3O4@SiO2@Tannic acid supplies an environmentally friendly procedure for the synthesis of some novel 5-amino-pyrazole-4-carbonitriles through the three-component mechanochemical reactions of synthetized azo-linked aldehydes, malononitrile, and phenylhydrazine or p-tolylhydrazine. These compounds were produced in high yields and at short reaction times. The catalyst could be easily recovered and reused for six cycles with almost consistent activity. The structures of the synthesized 5-amino-pyrazole-4-carbonitrile compounds were confirmed by 1H NMR, 13C NMR, and FTIR spectra, and elemental analyses.